Mother Tongue as a Medium for Faith Growth: A Study of Christian Religious Education in the Gudang Garam GIDI Congregation - Bernard Labobar; Ria Imelda Simanjuntak; Yohanna Ristua (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study stems from the issue of the weakening use of mother tongue in Christian Religious Education, particularly amid the dominance of the national language and the tide of modernisation that has the potential to erode the depth of the congregation's faith. This study aims to analyse the role of mother tongue as a medium for the growth of faith among the congregation of GIDI Gudang Garam in Kerom Regency. The research uses a qualitative method with a descriptive approach, based on a postpositivist paradigm. Data were collected through in-depth interviews, participatory observation, and documentation, then analysed using an interactive model. The findings show that the mother tongue functions strategically as a pedagogical, relational, and spiritual tool in faith education. The use of mother tongue allows God's word to be understood in a more personal, contextual, and existential manner, as well as strengthening the integration of Christian faith with local cultural identity. In addition, mother tongue encourages active participation of the congregation and deepens personal relationship with God, especially in worship, prayer, and children's faith education. This study concludes that mother tongue is an important foundation for deep-rooted, inclusive, and sustainable faith growth in the context of Christian Religious Education.